Dilemas na tradução de Muse & Drudge (Musa E Mula), de Harryette Mullen: negritude, dissonância e miscigenação - Amorim, Lauro Maia [UNESP] (My University, 2010)
This paper aims to discuss a project of translating part of the work Muse & Drudge, by the award-winning African-American poet Harryette Mullen, into Brazilian Portuguese, with focus on a single poem. In Muse & Drudge Mullen combines cultural critique with humor, lyricism and punning, which has unfolded the frontiers between cultural and racial identity, and has put into question the opposition between popular and high culture. This work analyzes to which extent the proposed translation produces a new set of intertextual relations that might culminate in “unexpected” meanings. It is a goal to understand how the effects of such “unexpected” meanings reveal the “encounter” between the so-called racial “black/white” dichotomy, predominant in the US culture, and the notion of “miscegenation” and “racial democracy” in Brazil.

O trabalho discute um projeto de tradução, para o português brasileiro, de um dos poemas da obra Muse & Drudge (“Musa e Mula”) da premiada poeta afro-americana Harryette Mullen. Em Muse & Drudge, Mullen entrelaça crítica cultural com humor, lirismo e trocadilhos que desdobram as fronteiras entre identidade cultural e racial, além de redimensionar os limites da oposição entre cultura popular e erudita. Pretende-se discutir em que medida a tradução proposta produz outras relações intertextuais que culminam com efeitos de sentido inesperados. Pretende-se também avaliar de que modo os interstícios desse “inesperado” revela o “encontro” entre as chamadas categorias raciais black e white, dominantes na cultura norte-americana, e a noção de miscigenação e “democracia racial” no Brasil.
Keywords: Translation; African-American poetry; miscegenation; dilemmas